Soviet Interest in Scandinavia: An Analysis of Soviet Foreign Policy toward the Nordic States. - Easterly,James C (1977)
Given the trend toward increased interdependence and regional integration in the European state system since World War II, plus the stark reality of strategic geography, this thesis postulates that Soviet foreign policy toward any of the Scandinavian states is best comprehended from a regional perspective. Soviet interactions with the Scandinavian states through the media of the Communist Party, interstate diplomacy, trade and armed force are taken as the collective expression of Soviet interests in the region, the roots of Soviet foreign policy. The plan and prognosis for Soviet foreign policy, faithfully attributed by today's Soviet leaders to the wisdom and vision of Party founders, Marx and Lenin, are examined in this thesis in the light of Scandinavia's political history to gauge Scandinavia's ideological potential for Soviet cultivation. (Author)